Analysis of Maintenance Priority Scale Determination of Permanent Way MRT Jakarta with Reliability Centered Maintenance Method - Andhita, Atria; Prihatanto, Rusman; Puruhita, Hana Wardani (Politeknik Perkeretaapian Indonesia Madiun, 2024)
Inspection and maintenance of infrastructure to maintain service life and to restore the function of railway components to match the replacement plan and ensure the feasibility and reliability of the MRT Jakarta operating system as planned. The priority scale of permanent way maintenance using the Reliability Centered Maintenance (RCM) method, especially on elevated lines, will be obtained for effective and efficient railway maintenance planning. With quartile calculations based on the criticality value of the first priority results, namely the location of the road or the Fatmawati Station - Cipete Raya Station corridor with a value of 41, the second priority on the Lebak Bulus Station - Fatmawati Station corridor with a value of 38, the third priority on the Cipete raya Station - Haji Nawi Station corridor with a value of 37, the fourth priority on the Blok A - Blok M Station corridor with a value of 36, the fifth priority on the haji Nawi - Blok A Station corridor with a value of 34, and on the sixth priority on the Blok M - ASEAN Station corridor with a total value of 29.